Integrating Language, Culture, and Communication in English Teaching: Enhancing Intercultural Communicative Competence - Maqsudova Oysara Nishonovna; Rustamov Firdavs Rafael o‘g‘li; Jumayev Bekzodjon To‘ra o‘g‘li (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This study explores the role of integrating language, culture, and communication in fostering Intercultural Communicative Competence (ICC) in English language classrooms. Drawing on the theoretical perspectives of Byram, Kramsch, Savignon, and Hymes, the paper examines foundational concepts, practical teaching strategies, and methodological approaches that encourage culturally responsive and communication-focused learning. The findings suggest that embedding cultural knowledge alongside authentic communicative tasks enhances student motivation, intercultural understanding, and overall linguistic proficiency.